Industrial Espionage and Technical Surveillance Counter Measurers - Androulidakis, I.I; Kioupakis, Fragkiskos - Emmanouil (Springer International Publishing : Imprint: Springer, 2016)
This book examines technical aspects of industrial espionage and its impact in modern companies, organizations, and individuals while emphasizing the importance of intellectual property in the information era. The authors discuss the problem itself and then provide statistics and real world cases. The main contribution provides a detailed discussion of the actual equipment, tools and techniques concerning technical surveillance in the framework of espionage. Moreover, they present the best practices and methods of detection (technical surveillance counter measures) as well as means of intellectual property protection.